Ocho ensayos de arqueosemiótica. Introducción e Índice. - Flores, Roberto (Revista Acta Semiotica, 2021)
Con las contribuciones de Göran Sonesson, Socorro C. de la Vega Doria, Emmanuel Alejandro Gómez Ambriz, Martín Cuitzeo Domínguez Núñez, Roberto Flores, Eric Landowski, Alejandro Olmos Curiel, Manar Hammad.